Survey of Treponemal Infections in Free-Ranging and Captive Macaques, 1999–2012 - Amy R. Klegarth; Chigozie A. Ezeonwu; Aida Rompis; Benjamin P.Y.-H. Lee; Nantiya Aggimarangsee; Mukesh Chalise; John Cortes; M. Feeroz; Barbara J. Molini; Bess C. Godornes; Michael Marks; Michael Schillaci; et al. (Emerging Infectious Diseases, 2017)
Survey results showed treponemal infection among pet macaques in Southeast Asia, a region with a high prevalence of human yaws. This finding, along with studies showing treponemal infection in nonhuman primates in Africa, should encourage a One Health approach to yaws eradication and surveillance activities, possibly including monitoring of nonhuman primates in yaws-endemic regions.